Analgesic Efficacy and Postoperative Outcomes of Serratus Anterior Plane Block in Patients Undergoing Coronary Artery Bypass Grafting via Median Sternotomy Approach - Sajjad, Ahsan; Hayat, Sikandar; Paracha, Vaqar Ilahi; Chaudhry, Imtiaz Ahmed; Akhtar, Usama; Tariq, Muhammad Mansoor (Indus Journal of Bioscience Research, 2025)
Background: Pain is common at sternotomy site after cardiac surgery. Managing such pain plays an important role in patient recovery. Various side effects are related to the traditional analgesic modalities. To minimize such effects several nerve blocks have been suggested. Objective: The aim of our study is to evaluate the analgesic efficacy of serratus anterior plane block (SAPB) in managing acute post sternotomy pain. Methodology: This randomized control trial included 240 patients between age 18 to 90 undergoing coronary artery bypass grafting (CABG) via median sternotomy approach. The study was conducted at Armed Forces Institute of Cardiology/National Institute of Heart Disease Rawalpindi Pakistan, for the duration of five months from October 2024 to February 2025. Patients were divided into two groups: serratus anterior plan block (SAPB) group which received 50mg of 0.25% bupivacaine diluted in 10 ml 0.9% normal saline on both sides and a control group which did not underwent any such intervention. Results: Intra-op fentanyl requirement was lower in SAPB group (221.38 ± 47.11 µg) as compared to control groups (297.22 ± 77.69 µg) (p value